Estimation of Extract Yield and Mass Transfer Coefficient in Solvent Extraction of Lubricating Oil - Hussain, Hussain K. (Al-Khwarizmi Engineering Journal, 2010)
An investigation was conducted to suggest relations for estimating yield and properties of the improved light lubricating oil fraction produced from furfural extraction process by using specified regression.Mass transfer in mixer-settler has been studied. Mass transfer coefficient of continuous phase, mass transfer coefficient of dispersed phase and the overall mass transfer coefficient extraction of light lubes oil distillate fraction by furfural are calculated in addition to all physical properties of individual components and the extraction mixtures.The effect of extraction variables were studied such as extraction temperature which ranges from 70 to 110°C and solvent to oil ratio which ranges from 1:1 to 4:1 (wt/wt) were studied.The results of this investigation show that the extract yield E decreased with decreasing solvent to oil ratio in extract layer and increased with increasing temperature. The fraction of total solvent in the raffinate phase decreased with increasing oil to solvent ratio in raffinate layer and increased with increasing temperature. Solvent to oil ratio in extract layer decreased with increasing temperature and increased with increasing solvent to charge oil ratio at constant temperature. Oil to solvent ratio in raffinate decreased with increasing temperature and increased with increasing solvent to charge oil ratio at constant temperature.Estimated functions are the best modeling function for prediction extraction data at various operating conditions. Mass transfer coefficient of continuous phase kc and  mass transfer coefficient of dispersed phase kd are increased with increasing temperature and solvent charge to oil ratio at constant temperature. The over all mass transfer coefficient  Kod  is increased with increasing temperature and solvent to charge oil ratio; while Kod a is increased with temperature and decreased with solvent to charge oil ratio.